Physical Activity Recommendations for Segments of School Days in Adolescents: Support for Health Behavior in Secondary Schools - Frömel, Karel; Groffik, Dorota; Mitáš, Josef; Madarasová Gecková, Andrea; Csányi, Tamás (Frontiers in Public Health, 2020)
School physical activity (PA) is an indispensable part of daily PA, the foundation for developing lifelong PA and fitness, and an easy way to gain physical and health literacy. School PA is equally important for understanding the continuity of physical and mental health, even in broader psychosocial aspects. Regarding long-term outcomes, significant attention has been paid to the determination of daily and weekly recommendations for adolescent PA. However, comprehensive approaches suggesting recommendations for PA in segments of the school day are rare. This study aimed to (a) provide a rationale for PA recommendations in segments of school days and incorporate it into generally accepted PA recommendations, and (b) promote radical changes in the educational process toward a healthy school lifestyle through PA recommendations in segments of school days. The results of research conducted in 98 secondary schools in the Czech Republic and 104 secondary schools in Poland from 2009 to 2017 were used in this study. In total, 3,860 boys and 5,237 girls from the Czech Republic and 3,052 boys and 3,329 girls from Poland, all aged 15–19, participated. We recommended at least 2,000 steps (or 10 min of moderate-to-vigorous PA) for the before school segment and at least 6,000 steps (or 30 min of moderate-to-vigorous PA) for the after-school segment. For the time spent at school, we further recommended at least 500 steps/h (alternatively, at least 3,000 steps/school time), 20 min of moderate-to-vigorous PA (≥3METs or 60% HRmax), and at least one HRsubmax/max response to significant stress during PA to mitigate educational stress and high levels of sedentary behavior in schools. PA should account for at least 25% of school time, even on days with no scheduled physical education lessons. We propose using PA recommendations in segments of school days to achieve positive changes in the educational process and school lifestyle. Acceptance of PA recommendations in segments of school days theories on physical education could help refine and concretize demands for changes in PA and lifestyle in secondary schools. In practice, it could support the creation of innovative and comprehensive school PA programs. Future research should focus on obtaining evidence in support for adolescent PA by applying PA recommendations in segments of school days.